Emergency peripartum hysterectomy: Experience of a major referral hospital in Ankara, Turkey. (January 2015) - Danisman, N.; Baser, E.; Togrul, C.; Kaymak, O.; Tandogan, M.; Gungor, T.
Abstract The objective of this study was to report and discuss the incidence, clinical characteristics and outcomes of emergency peripartum hysterectomies (EPH) performed at a tertiary referral hospital in Ankara, Turkey. The labour and delivery unit database was retrospectively analysed for emergency peripartum hysterectomies (EPH) performed between January 2008 and January 2013, at the Zekai Tahir Burak Women's Health Training and Research Hospital. A total of 92, 887 deliveries were accomplished within the study period. EPH was performed in 48 cases, and the incidence was 0.51 in 1, 000. Abnormal placentation was the most common indication for EPH. Most common complications were blood product transfusion and postoperative fever. None of the cases resulted in maternal mortality. Serious maternal complication rates were relatively low in our study. In cases that are unresponsive to initial conservative measures, EPH should be performed without delay and a multidisciplinary team approach should be conducted whenever possible.